Pengembangan Media Big Book Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Bercerita Anak Usia Dini - Marfuah, Siti; Sulianto, Joko; Nugroho, Aryo Andri; Tajqiyah, Lina (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Findings related to the low storytelling ability of young children and the need for learning media that can support storytelling learning are the background for this research. The aim of the research was to analyze the need, practicality and effectiveness of PBL-based Big Book media in improving the storytelling skills of young children. This research methodology is research and development (R&D). The sampling technique used in this research was total sampling. The research instruments were observation sheets and questionnaires. Data analysis uses descriptive analysis and t test. The research results show that PBL-based Big Book media meets the elements of validity, practicality and effectiveness and can be used in learning. The validation results of the two experts stated that PBL-based Big Book media was very feasible, where the material score was 84.6% and the media score was 88.0%. The media effectiveness test showed that the ability to tell stories in the experimental class (86%) was higher than the control class (68%). The difference test found that the mean storytelling ability of the experimental class was significantly different from the control class (p=0.000). Thus, it is concluded that PBL-based Big Book media is quite effective in improving storytelling abilities in young children.